2022
DOI: 10.1016/j.ejvs.2021.09.032
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen Sulphide Release via the Angiotensin Converting Enzyme Inhibitor Zofenopril Prevents Intimal Hyperplasia in Human Vein Segments and in a Mouse Model of Carotid Artery Stenosis

Abstract: WHAT THIS PAPER ADDSThe current strategies to reduce intimal hyperplasia (IH) rely principally on local drug delivery, in an endovascular approach. The oral angiotensin converting enzyme inhibitor (ACEi) zofenopril has additional effects to other non-sulfyhydrated ACEi to prevent intimal hyperplasia and re-stenosis. Given the number of patients treated with ACEi worldwide, these findings call for further prospective clinical trials to test the benefits of sulfhydrated ACEi over classic ACEi for the prevention … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 11 publications
(27 citation statements)
references
References 28 publications
0
25
1
Order By: Relevance
“…On the contrary, CSE overexpression decreases IH formation in a murine model of vein graft by carotid-interposition cuff technique (Trocha et al, 2020). We and others demonstrated that several H 2 S donors inhibit IH in vivo in various models in rats (Meng et al, 2007), rabbits (Ma et al, 2012), mice (Yang et al, 2012;Macabrey et al, 2022a;Macabrey et al, 2022b), and in human great saphenous vein segments ex-vivo (Longchamp et al, 2019;Macabrey et al, 2022a;Macabrey et al, 2022b). H 2 S also directly inhibits VSMC proliferation and migration (Yang et al, 2006;Ma et al, 2012;Longchamp et al, 2019).…”
Section: Role Of Ec Dysfunctionmentioning
confidence: 94%
See 1 more Smart Citation
“…On the contrary, CSE overexpression decreases IH formation in a murine model of vein graft by carotid-interposition cuff technique (Trocha et al, 2020). We and others demonstrated that several H 2 S donors inhibit IH in vivo in various models in rats (Meng et al, 2007), rabbits (Ma et al, 2012), mice (Yang et al, 2012;Macabrey et al, 2022a;Macabrey et al, 2022b), and in human great saphenous vein segments ex-vivo (Longchamp et al, 2019;Macabrey et al, 2022a;Macabrey et al, 2022b). H 2 S also directly inhibits VSMC proliferation and migration (Yang et al, 2006;Ma et al, 2012;Longchamp et al, 2019).…”
Section: Role Of Ec Dysfunctionmentioning
confidence: 94%
“…Frontiers in Physiology frontiersin.org pathway (Macabrey et al, 2022a). H 2 S also limit MMP2 expression and ECMs degradation, reducing VSMCs migration (Yang et al, 2010;Yang et al, 2012).…”
Section: Role Of Ec Dysfunctionmentioning
confidence: 99%
“…All conditions were tested in parallel. Cells were fixed in ice-cold methanol 100 and immunostained for BrdU as previously described ( 23 , 26 , 30 ). Images were acquired using a Nikon Eclipse 90i microscope.…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, Zofenopril prevents IH in an ex vivo model of IH in human saphenous vein. The effect of Zofenopril on IH correlates with reduced VSMC proliferation and migration and decreased activity of the MAPK and mTOR pathways ( 138 ).…”
Section: Discussion: New Perspectives For the Treatment Of Intimal Hp...mentioning
confidence: 99%